Exercising motherhood and fatherhood among persons with disabilities: An analysis from the perspective of education (Palimpsesto, 2025)
This study examines motherhood and fatherhood among people with disabilities in Chile, focusing on educational level as the main axis of analysis. Using a mixed-method approach, the association between educational level and the condition of being a mother or father with a disability was characterized and evaluated, the assessment of access to information and training on sexual and reproductive health was described, and parental experiences in the school context were explored. The results indicate that the internet is the main source of information on sexual and reproductive health. Physical, communication, and attitudinal barriers were also identified that limit access to information and participation in the school life of children, highlighting shortcomings in support for parenting.
Keywords: disability; reproductive health; parenting; education; access to information